Contextual Learning and Teaching to Improve Students Understanding of Aqidah and Akhlak - Lailatul Hamidah Al Maqi (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2024)
Classroom action research analyzes the effectiveness of contextual learning and teaching to improve understanding of aqidah and akhlak. Classroom action was carried out in Class 7 of Madrasah Tsanawiyah. The results of the classroom action show that contextual learning and teaching enable students to connect the concepts of honesty and responsibility with everyday life. The principle of constructivism helps students build understanding through direct experience. The community of inquiry and learning increases student engagement in exploring the values ​​of aqidah and akhlak. Modeling provides concrete examples that students can imitate. Authentic reflection and assessment measure student understanding and behavioral changes. Contextual learning and teaching successfully improve student understanding and participation. There are challenges in ensuring equal involvement among all students. Additional strategies such as simulation and role-playing are recommended to further optimize learning effectiveness. Contextual learning and teaching are effective in linking aqidah and akhlak material with students’ real experiences, strengthening understanding and application of Islamic values ​​in everyday life.